A new genus and species of catshark (Carcharhiniformes: Scyliorhinidae) from eastern Indonesia - White, William T.; Fahmi, Fahmi; Weigmann, Simon (Zootaxa, 2019)
A new genus and species of catshark is described based on a single specimen collected off Ambon in the Maluku Islands of eastern Indonesia. Akheilos suwartanai belongs to the subfamily Schroederichthyinae which differs from the other catsharks in a combination of: similar sized dorsal fins, supraorbital crests present, pseudosiphon present on claspers, broad subocular ridges under eyes, posterior nasal flaps present, tips of rostral cartilage fused into a rostral node. It represents the first record of this subfamily outside of the Americas. Akheilos differs from the other genus in the subfamily, Schroederichthys in a combination of: clasper groove not fused dorsally, ventral lobe of caudal fin produced, more intestinal valve turns, anal fin slightly larger than second dorsal fin, and in colour pattern.